Limited Evidence for Parallel Evolution Among Desert-Adapted Peromyscus Deer Mice. (4th March 2021) - Colella, Jocelyn P; Tigano, Anna; Dudchenko, Olga; Omer, Arina D; Khan, Ruqayya; Bochkov, Ivan D; Aiden, Erez L; MacManes, Matthew D
Abstract: Warming climate and increasing desertification urge the identification of genes involved in heat and dehydration tolerance to better inform and target biodiversity conservation efforts. Comparisons among extant desert-adapted species can highlight parallel or convergent patterns of genome evolution through the identification of shared signatures of selection. We generate a chromosome-level genome assembly for the canyon mouse ( Peromyscus crinitus ) and test for a signature of parallel evolution by comparing signatures of selective sweeps across population-level genomic resequencing data from another congeneric desert specialist ( Peromyscus eremicus ) and a widely distributed habitat generalist ( Peromyscus maniculatus ), that may be locally adapted to arid conditions. We identify few shared candidate loci involved in desert adaptation and do not find support for a shared pattern of parallel evolution. Instead, we hypothesize divergent molecular mechanisms of desert adaptation among deer mice, potentially tied to species-specific historical demography, which may limit or enhance adaptation. We identify a number of candidate loci experiencing selective sweeps in the P. crinitus genome that are implicated in osmoregulation ( Trypsin, Prostasin ) and metabolic tuning ( Kallikrein, eIF2-alpha kinase GCN2, APPL1/2 ), which may be important for accommodating hot and dry environmental conditions.